Publishing Thoughts from the Bed Sorbonne: Toward A Crip Publishing Manifestx - Przybyło, Ela (Imaginations)

(untitled) (York University, 2025)
In this piece I draw on my experiences as a neuroqueer editor of the peer-reviewed, intersectional, and intermedia independent journal Feral Feminisms and on disability justice to hone a short manifestx on crip publishing. While peer-reviewed journals often demand free, invisible, and feminized labor along with high-speed efficiency, I imagine crip approaches to publishing as necessitating such principles as slowness, anti-fascism, recognition, care, failure, multiple mediums for knowledge-making, and community building. The piece begins with a reflection from the “Bed Sorbonne” or academic’s bed office, and moves into a consideration of how thinking sustainable publishing with lichen can enliven our publishing praxes. Finally, I outline the nine part manifestx as a starting point for imagining crip informed publication models. The hybrid and art-based piece engages with the theme of sustainable publishing by thinking about how to make publishing sustainable—as in doable, feasible, possible, limitless— both for crip authors/creators and crip journal editors.